The Impact Of Application Principles Of Corporate Governance On The Share Price Of The Banks Listed On The Damascus Stock Exchange - نادر نهاد; جديد صبا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to test the effect of applying the principles of corporate governance on the share price, to find out the importance of governance in relation to the share price, as the researcher relied on testing nine principles approved by the Syrian Securities Commission, and carried out a comprehensive study of all banks listed on the Damascus Stock Exchange, and was adopted in This is based on the analytical deductive approach for the period extending from 2010 to 2018, and the most important findings of the researcher are that there is an impact (ownership of the largest shareholder, ownership of legal shareholders, dividend policy, capital increase) while there is no effect ( Due to the existence of a special section for shareholder relations), on the share price of the banks listed on the Damascus Stock Exchange, meaning that most of the principles of corporate governance had an effect, so the researcher recommended through This study indicates that banks should adhere to the policy of dividend distribution and increasing capital, in addition to increasing the importance of forming audit committees and for all of their members to be independent, and for banks to seek not to exceed the percentage of legal shareholders, Also, it does not necessarily adhere to the percentage established by the principles of corporate governance regarding ownership of the largest shareholder.